Newly discovered rock art sites in Balandar, Mashhad province, north-eastern Iran. (5th June 2017) - Sigari, Dario; Toghrae, Mahmoud; Basafa, Hassan
Abstract : The site of Pire Mazar Balandar (or PMB001) is located near the village of Balandar in the Khorasan region of north-eastern Iran (33°09′37.64′′N, 59°29′52′′E;Figure 1 ). It consists of an outcrop of volcanic rock on a mountain peak (1532m asl) on the north-eastern side of the Binaloud range, above the city of Mashhad (Figure 2 ).